Types of Epiphytic Orchids (Orchidaceae) in Coffe plantations in Simpang Teritit Village, Wih Pesam District, Bener Meriah Regency - Selvi Ulan Dari; Cut Nurmaliah; Hasanuddin Hasanuddin; Djufri Djufri; Dewi Andayani (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Epiphytic orchids are orchids that live attached to the trunk, branches, or twigs of both living and dead trees. Research on